ANTHROPOMETRI PEKERJA INDUSTRI DAN PERTANIAN DI BEBERAPA NEGARA TERTENTU: SEBUAH STUDI LITERATUR - Robertoes Koekoeh Koentjoro Wibowo (ROTOR, 2016)
Research on anthropometry has been widely carried out using different objects and methods. The researchers conducted a study with measurements of anthropometric dimensions to body dimensions in particular where the number of body dimensions which measures are different among studies. Thus the result of measurements of body dimensions of each study is not the same. However there are having similar method of research on the measurement of the same body dimensions. Body dimensions data that obtained from measurements can be used as designers reference in the design of ergonomic tools or machinery. From the anthropometric data in the same industry and agriculture workers can be done several comparative dimensions of the body of workers and farmers. This study is comparing anthropometric of worker among in industrial population and among agricultural workers/ farmer. Base on review of data, the study has resulted that each people in different country has its own characteristic form of body dimensions which differ from another. The comparison of body dimensions among workers who work in industrial show that they have variation Mean (M) value of body dimension. Characteristic body dimension of Algerian agriculture workers, except foot breadth, have highest Mean (M) value compare with others countries. Thai female agriculture workers have lower Mean (M) value of body dimension in almost all parts compare with others countries. Keywords: anthropomety, industrial, agriculture